Transaminase and phosphatase activity of blood and seminal plasma in breeding bulls of different breeds - DHAMI, A J; SHELKE, VINAYA B; VIRANI, A C; KAVANI, F S; DAVE, R R (The Indian Journal of Animal Reproduction, 2023)
The normal profile of blood plasma and seminal plasma transaminases and phosphatases was studied twice at monthly interval in 37 breeding bulls ofGir, Holstein Friesian, Jersey, Crossbred and Jafarabadi breeds. The differences between breeds were significant (P<0.01) for only AKP and AKP:ACP ratio in blood and for all enzymes, except GOT, in seminal plasma. The lowest and highest GOT:GPT ratio was observed in blood of crossbred and Jersey/Jafari, and in the seminal plasma of Jersey and HF/crossbred bulls respectively. Similarly, the AKP:ACP ratio in blood was lowest in Jersey and highest in Gir. In seminal plasma it was lowest in Jersey and highest in HF/Jafari bulls. The levels oftransaminases were nearly identical both in blood and seminal plasma of all the breeds, but AKP and ACP levels were much lower (20-20() times) with higher AKP:ACP ratios (3-7 times) in blood than the seminal plasma of same bulls.